Correction: In silico and in vitro metabolism of ribociclib: a mass spectrometric approach to bioactivation pathway elucidation and metabolite profiling. Issue 40 (23rd June 2020) - Alsubi, Thamer A.; Attwa, Mohamed W.; Bakheit, Ahmed H.; Darwish, Hany W.; Abuelizz, Hatem A.; Kadi, Adnan A.
Abstract : Correction for ' In silico and in vitro metabolism of ribociclib: a mass spectrometric approach to bioactivation pathway elucidation and metabolite profiling' by Thamer A. Alsubi et al., RSC Adv., 2020, 10, 22668–22683, DOI: ; 10.1039/D0RA01624A .